Comparative Analysis of the EU Public Sector Internal Audit Methodology and Requirements - Faitusa, Ivita; Grima, Simon; Baldacchino, Peter J. (University Latvia, Faculty of Economics and Management, 2016)
Abstract. There is currently no standard or requirement guiding the approaches taken by the European Union (EU) Public Sector internal audit. Therefore, the approaches taken by each country, although having some similarities are different. The aim of this research is to compare the Latvian state administration internal audit approach with approaches of the following specific European countries: United Kingdom, Malta, Estonia, Lithuania, Latvia and Poland and evaluate each country’s internal audit approach according to internal audit maturity determinants. The latter have been determined from literature, the Compendium report. Thereby, shedding light on the Latvian’s internal audit approach maturity. The methodology includes a comparative study of 5 European countries’ public sector internal audit methodologies, by carrying out a documents analysis and evaluation of the existing normative acts, analysing cases and other scientific findings of internal audit methodology and legislation. Authors recommend introducing a common internal audit procedures manual, standards and guidelines for the public sectors in the EU Member States. They believe that this will improve internal controls and internal audit data analysis around Europe. The main results of the study will highlight the maturity of each of these countries’ internal audit approaches and their pros and cons. It will also highlight where improvements might be required or where changes are necessary. Keywords: internal audit, public sector, internal control JEL code: M42
Keywords: internal control; Public sector; Internal audit